Regional Autonomy as a Form of Constitutional Reform In Aspirational Governance - Yogi Prasetyo (Fakultas Hukum Universitas Lampung, 2021)
This paper is a study of research results that aims to explain the birth of local autonomy from the results of constitutional reform as a form of governance following the community's aspirations. In the past, the problem of the centralized government system did not provide opportunities for regions to regulate and manage their regional government. It was considered undemocratic and did not bring progress to the people in the regions. Therefore, significant changes to the government system in the most aspirational areas through local autonomy are needed. This study, using a normative juridical research method with a philosophical approach. The research results obtained an understanding of the existence of local autonomy as a form of constitutional reform, which is the aspiration of the will of the people in the regions. With the constitutional reform, the system has changed to become decentralized. It has a closer relationship with the people in the regions and can understand the needs of the lower classes. The constitution, with its amendments, can create a democratic system of government and ensure public participation in the life of the state.